2023
DOI: 10.1002/jcp.30944
|View full text |Cite
|
Sign up to set email alerts
|

GALR2 and Y1R agonists intranasal infusion enhanced adult ventral hippocampal neurogenesis and antidepressant‐like effects involving BDNF actions

Abstract: Dysregulation of adult hippocampal neurogenesis is linked to major depressive disorder (MDD), with more than 300 million people diagnosed and worsened by the COVID‐19 pandemic. Accumulating evidence for neuropeptide Y (NPY) and galanin (GAL) interaction was shown in various limbic system regions at molecular‐, cellular‐, and behavioral‐specific levels. The purpose of the current work was to evaluate the proliferating role of GAL2 receptor (GALR2) and Y1R agonists interaction upon intranasal infusion in the ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 96 publications
4
11
0
Order By: Relevance
“…[50][51][52][53] However, this observation is particularly relevant considering speciesspecific differences in antidepressant responses between rats and mice, 75 as evidenced by studies on mice showing antidepressant-like effects of a spexin-based GALR2 agonist within 2-3 h. 76 The role of the GALR2 antagonist M871 in counteracting the enhanced response observed further substantiates the specific involvement of GALR2 and NPY1R in these effects. 41,43 Our also previous research indicating the involvement of the ventral hippocampus in the antidepressant effects of NPY in conditions like posttraumatic stress disorder 77 and the higher expression of NPY1R in the ventral compared to the dorsal hippocampus. 58 While the observed antidepressant-like effects of NPY1R and GALR2 agonist co-administration persisting for 3 weeks post-treatment represent a significant finding, extending the analysis beyond this timeframe presents logistical and ethical challenges.…”
Section: Galr2 and Npy1r Agonists: Implications For Antidepressant-li...supporting
confidence: 74%
See 3 more Smart Citations
“…[50][51][52][53] However, this observation is particularly relevant considering speciesspecific differences in antidepressant responses between rats and mice, 75 as evidenced by studies on mice showing antidepressant-like effects of a spexin-based GALR2 agonist within 2-3 h. 76 The role of the GALR2 antagonist M871 in counteracting the enhanced response observed further substantiates the specific involvement of GALR2 and NPY1R in these effects. 41,43 Our also previous research indicating the involvement of the ventral hippocampus in the antidepressant effects of NPY in conditions like posttraumatic stress disorder 77 and the higher expression of NPY1R in the ventral compared to the dorsal hippocampus. 58 While the observed antidepressant-like effects of NPY1R and GALR2 agonist co-administration persisting for 3 weeks post-treatment represent a significant finding, extending the analysis beyond this timeframe presents logistical and ethical challenges.…”
Section: Galr2 and Npy1r Agonists: Implications For Antidepressant-li...supporting
confidence: 74%
“…This observation is in line with our previous reports on the short-term actions of these agonists in various brain regions, including the amygdala and hippocampus. [36][37][38]40,43 Additionally, the involvement of 5HT1A-FGFR1 heteroreceptor complexes in stimulating hippocampal plasticity linked to antidepressant-like actions further supports this mechanism. 78,79 The evaluation of NPY1R-GALR2 PLA numbers in the ventral hippocampus could serve as a unique biomarker for single-cell resolution, demonstrating drug target engagement with localized precision.…”
Section: Cellular Mechanisms Underlying the Antidepressant-like Actionsmentioning
confidence: 70%
See 2 more Smart Citations
“…As shown in Figure A, a total of 152 genes were upregulated and 157 genes were downregulated in the Ri@EGCG-2 NP group compared with the SCI group. Remarkably, among the upregulated genes in the Ri@EGCG-2 NP group, there were numerous genes related to SCI repair including nerve regeneration, synaptic remodeling, and extracellular mechanism remodeling (Figure B), such as Galr2, Mospd4, Lilrb3a, Col22a1, Col2a1, etc. Similarly, the significant enrichments in Gene Ontology (GO) biological processes (BP), molecular function (MF), and cellular component (CC) (Figure C, Figures S16 and S17) showed that the pathways related to stem cell proliferation, axon regeneration, neuron regeneration, synaptic remodeling, and extracellular matrix remodeling were significantly enriched in the Ri@EGCG-2 NPs group compared with the SCI group. To confirm the results of RNA sequencing, sections and immunofluorescence staining were performed on the spinal cord tissue at the injury site. As shown in the immunofluorescence staining with DAPI and Nestin (to label neural stem cells (NSCs)) images in Figure D and quantitative analysis in Figure E, there was a small amount of Nestin-positive NSCs in SCI groups, and more noticeable Nestin-positive NSCs filled the injury site in the Ri@EGCG-2 NPs group.…”
Section: Resultsmentioning
confidence: 95%